Theta phase‐gamma amplitude coupling during working memory and its relationships with demographic, clinical, genetic, neurochemical, and neurostructural measures in older adults at risk for dementia. (31st December 2021) - Patterson, Rachel A.; Brooks, Heather J.; Mirjalili, Mina; Rashidi‐Ranjbar, Neda; Zomorrodi, Reza; Blumberger, Daniel M.; Kumar, Sanjeev; Fischer, Corinne E.; Flint, Alastair; Graff‐Guerrero, Ariel; Herrmann, Nathan; Kennedy, James L.; et al.
Abstract: Background: Theta phase‐gamma amplitude coupling (TGC) is a neurophysiological mechanism that underlies working memory (WM) 1 . WM is also associated with demographic, clinical, genetic and neuroimaging measures. However, the relative contributions of TGC and these measures to WM, and the relationship between TGC and these measures, remains unclear. We examined the relative contributions of TGC and these measures to WM performance in a group of participants at‐risk for Alzheimer's dementia. Method: Older participants (age=71.2±6.0, N = 206) with Mild Cognitive Impairment (MCI), Major Depressive Disorder (MDD), or MCI+MDD completed clinical assessment, N‐back WM task with EEG to measure TGC, genetic testing, PET with [ 11 C]‐Pittsburgh Compound B ([ 11 C]‐PIB PET) and brain 3T MRI. Linear regressions were used to assess the relationships among 2‐back WM performance; demographic and clinical variables; TGC; ApoE4 carrier status; total beta‐amyloid SUVR ([ 11 C]‐PIB PET); and regional cortical thickness, subcortical volumes, and white matter fractional anisotropy (MRI). Result: 2‐back WM performance was associated with age and TGC after controlling for all other measures (Age: β=‐0.253; p=0.039, TGC: β=0.300; p=0.005). TGC was not associated with any other measures after correction for multiple comparisons. Conclusion: TGC predicts WM performance in contrast to demographic, clinical, genetic, and PET and MRI imaging measures. Our findings underline the strong association between WM and TGC, a dynamic time‐based neurophysiological measure that is capturing a functional process which may not be captured by these static measures. Future studies could explore other dynamic measures with other imaging modalities and their relationships with TGC or other neurophysiological measures. 1. Rajji, T.K., et al., Ordering Information in Working Memory and Modulation of Gamma by Theta Oscillations in Humans. Cerebral Cortex, 2017. 27(2): p. 1482‐1490.